2015
DOI: 10.1088/2041-8205/804/1/l7
|View full text |Cite
|
Sign up to set email alerts
|

LABORATORY PHOTO-CHEMISTRY OF PAHs: IONIZATION VERSUS FRAGMENTATION

Abstract: Interstellar Polycyclic Aromatic Hydrocarbons (PAH) are expected to be strongly processed by Vacuum Ultra-Violet (VUV) photons. Here, we report experimental studies on the ionization and fragmentation of coronene (CH), ovalene (CH) and hexa-peri-hexabenzocoronene (HBC; CH) cations by exposure to synchrotron radiation in the range of 8-40 eV. The results show that for small PAH cations such as coronene, fragmentation (H-loss) is more important than ionization. However, as the size increases, ionization becomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 41 publications
8
44
0
Order By: Relevance
“…The complete chemistry of PAH species in the ISM, however, comprises other mechanisms, e.g., ion-neutral reactions, electron attachment, double ionization, and multiphoton processes, which have been evaluated with various models (Le Page et al 2001Page et al , 2003Montillaud et al 2013). In support to double ionization, a recent experimental study by Zhen et al (2015) concluded that, in the ISM, photoionization prevailed over fragmentation in PAH species containing about 50 C atoms and more, leading to the formation of doubly and even triply charged cations. As a consequence, these large species were found to be photostable in interstellar conditions, in agreement with previous theoretical studies (Allain et al 1996a;Montillaud et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The complete chemistry of PAH species in the ISM, however, comprises other mechanisms, e.g., ion-neutral reactions, electron attachment, double ionization, and multiphoton processes, which have been evaluated with various models (Le Page et al 2001Page et al , 2003Montillaud et al 2013). In support to double ionization, a recent experimental study by Zhen et al (2015) concluded that, in the ISM, photoionization prevailed over fragmentation in PAH species containing about 50 C atoms and more, leading to the formation of doubly and even triply charged cations. As a consequence, these large species were found to be photostable in interstellar conditions, in agreement with previous theoretical studies (Allain et al 1996a;Montillaud et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there should be no small, hydrogenated, carbon dust grains in the "ordinary" ISM, since they are very rapidly transformed into aromatic grains. The restructuring of larger dust grains takes longer: when [72], according to which ionization dominates for photon energies from 8 to 40 eV only for large dust grains, while a more important channel for small dust grains is their dissociation (loss of a hydrogen atom).…”
Section: Contribution Of Various Factors To Aromatization and Destrucmentioning
confidence: 99%
“…This fragmentation follows the available pathways (i.e., dehydrogenation or loss of C 2 or C 2 H 2 units), producing PAH derivative species along a top-down chemical scenario (Zhen et al 2014a;Bouwman et al 2016;Petrignani et al 2016). Photoionization and photofragmentation compete, and their relative importance depends on both the geometry of PAH molecules and the excitation wavelengths used (Zhen et al 2015(Zhen et al , 2016). …”
Section: Introductionmentioning
confidence: 99%